STUDI BIONOMIK VEKTOR MALARIA DI KECAMATAN KALIBAWANG, KULONPROGO - Sardjito Eko Windarso dkk (Jurnal Rekayasa Lingkungan)
The increasing of malaria cases in recent years at Kecamatan Kalibawang has been suspected correspond with the conversion of farming land-use which initiated in 1993. Four years after the natural vegetation in this area were changed become cocoa and coffee commercial farming estates, the number of malaria cases in 1997 rose more than six times, and in 2000 it reached 6085. This study were aimed to observe whether there were any differences in density and diversity of Anopheles as malaria vector between the cocoa and mix farming during dry and rainy seasons. The results of the study are useful for considering the appropriate methods, times and places for mosquito vector controlling. The study activities comprised of collecting Anopheles as well as identifying the species to determine the density and diversity of the malaria vector. Both activities were held four weeks in dry season and four weeks in rainy season. The mea-surement of physical factors such as temperature, humidity and rainfall were also conducted to support the study results. Four dusuns which meet the criteria and had the highest malaria cases were selected as study location. Descriptively, the results shows that the number of collected Anopheles in cocoa farming were higher compared with those in mix horticultural farming; and the number of Anopheles species identifi ed in cocoa farming were also more varied than those in the mix horticultural farming.Key words: bionomik vektor malaria, anopheles,